Environment and dengue in districts of Aracaju - Fonseca, V.; Soares, A. C. G. M.; Madi, R. R. (Scientia Plena, 2012)
Since the year 1999 many actions have been developed to combat dengue, but the number of cases is still very large and is growing in some states, such as Sergipe, which between 2010 and the 26 first weeks of 2011, grew 644%. Aracaju is showing the same problem, but with different intensities in various urban districts. This article examines the reported dengue cases in the Health Department of the Municipality of Aracaju, by urban districts, correlating the volume registered with the socio-environmental conditions of each district. The higher frequency of occurrence of dengue in some quarters, seems to be directly linked to the existence of environmental problems resulting from inappropriate land occupation, improper installation of basic infrastructure, lack of maintenance / conservation of the built environment, the existence of vacant lots, existence of buildings that constitute a store of value and real estate are vacant and in early stage of degradation. Added to these factors of the built environment, lack of commitment to the general populations, whose behavior leads to the proliferation of multiple small focus of the mosquito, usually their own house.